A beginners guide to literature in the field of aeroelasticity - Battoo, R. S. (Cranfield University, 1997)
This document is meant primarily for students (or readers) who may not be familiar with the field of aeroelasticity. The main objective of this paper is to point the reader to some important texts and papers that have been published in the areas which embrace aeroelasticity, using which the reader may gain sufficient knowledge about the subject to make informed decisions. It is hoped that by drawing the readers attention to these salient papers the more interested readers will be able to increase their knowledge on many aspects related to aeroelasticity. This paper is not meant to be exhaustive, rather it is meant to be a preliminary exposition which will assist readers in locating/selecting other relevant references or texts. This paper does not attempt to be an expert guide nor direct the reader to publications in a specific area. What it does attempt to do is hopefully generate interest and illuminate areas related to the field of aeroelasticity which readers can explore to their desire. A modestly comprehensive list of references is included, however it must be emphasized that there are a very extensive number of papers published each year, in all related fields of aeroelasticity. Inclusion of all these would not be appropriate in a paper of this kind. Never-the-less the more interested reader will find sufficient information to utilize the given citations for locating further material.